Effects of Anti-Cytokine Antibodies on Gut Barrier Function - Liu, Fang; Lee, Seul A.; Riordan, Stephen M.; Zhang, Li; Zhu, Lixin (Mediators of Inflammation, 2019)
Anti-cytokine antibodies are used in treating chronic inflammatory diseases and autoimmune diseases such as inflammatory bowel disease and rheumatic diseases. Patients with these diseases often have a compromised gut barrier function, suggesting that anti-cytokine antibodies may contribute to the re-establishment of gut barrier integrity, in addition to their immunomodulatory effects. This paper reviews the effects of anti-cytokine antibodies on gut barrier function and their mechanisms.